PENGARUH SIKAP WAJIB PAJAK DAN PENERAPAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (WAJIB PAJAK ORANG PRIBADI DI KOTA BANDUNG TAHUN 2016) - N. Heriyah (LPPM UNIBI, 2018)
The number of taxpayers from year to year is increasing but there are still obstacles that can hamper efforts to increase tax ratio, the obstacle is tax compliance (tax compliance). Several factors that can influence taxpayer compliance are taken in this study is the attitude of taxpayers, and the application of tax penalties. This study was conducted to assess the level of taxpayer compliance, especially private persons in the city of Bandung by using these independent variables. Variables of taxpayer attitude, and the application of tax sanction are chosen because it tends to be more in line with individual taxpayer compared with other variables. Because the two variables are directly related to how the individual taxpayers will determine the attitudes of the taxpayer on taxpayer compliance, and individual taxpayers when associated with the application of tax sanctions on compliance taxpayer. Population in this research is individual taxpayer residing in Bandung City. Based on data obtained from five Primary Tax Office in Bandung until 2016 was recorded as many as 749,929 people who is an effective personal taxpayer. Not all the effective individual taxpayers are subject to the research because of their huge amounts, therefore for the efficiency of time and costs sampling is taken. Sampling was done on 400 people by using probability sampling method. The primary data collection method used is by questionnaire method, while the data analysis technique used in this research is multiple linear regression analysis technique. Based on the results of the analysis conducted then obtained the conclusion that the attitudes of taxpayers, and tax penalties sanction have a significant positive effect on taxpayer compliance either simultaneously or partially. Keywords: Taxpayer Compliance, Taxpayer Attitude, and Implementation of Taxation Sanctions.